2023
DOI: 10.3390/diagnostics13030529
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of Single-Incision Laparoscopic Herniorrhaphy in Newborns and Infants

Abstract: Background: As surgical techniques progress, laparoscopic herniorrhaphy is now performed more often in premature babies. The aim of this study was to analyze the outcomes of newborns and infants who underwent single-incision laparoscopic herniorrhaphy (SILH) at our center. Methods: We retrospectively reviewed patients younger than 12 months old who received SILH at our department from 2016 to 2020. SILH involved a 5 mm 30-degree scope and 3 mm instruments with a 3-0 Silk purse-string intracorporeal suture for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…Patkowski et al reported an overall anaesthesia time of 48 minutes [11], which is significantly longer when compared to our data. In a study comparing single-incision laparoscopic herniorrhaphy (SILH) in newborns and infants, the average time under anaesthesia was reported to be 80.0 ± 14.5 minutes for newborns and 76.3 ± 12.9 minutes for infants (p=0.07) [13]. Average anaesthesia times in our study appear to be lower than those in the literature.…”
Section: Discussioncontrasting
confidence: 65%
“…Patkowski et al reported an overall anaesthesia time of 48 minutes [11], which is significantly longer when compared to our data. In a study comparing single-incision laparoscopic herniorrhaphy (SILH) in newborns and infants, the average time under anaesthesia was reported to be 80.0 ± 14.5 minutes for newborns and 76.3 ± 12.9 minutes for infants (p=0.07) [13]. Average anaesthesia times in our study appear to be lower than those in the literature.…”
Section: Discussioncontrasting
confidence: 65%
“…[ 9 ] One of the 3 cases occur before the age of 6 months, and the incidence in males is almost 5 to 10 times compared to females. [ 10 , 11 ] Incarceration may occur in 1/6 of indirect inguinal hernias. [ 12 ] When incarceration occurs in an inguinal hernia, it causes an irreducible mass in the groin or scrotum, along with tenderness, redness, and swelling, accompanied by nausea and vomiting, as well as other symptoms.…”
Section: Discussionmentioning
confidence: 99%